Guess what!? - Willems, Mo (New York, NY : Hyperion Books for Children, an imprint of Buena Vista Books, 2021)
"Zoom Squirrel and the Squirrel pals are looking forward to going to the beach"-- Provided by publisher.
Ages 4-8.
Grades 2-3.
Keywords: Squirrels -- Fiction; Beaches -- Fiction; Friendship -- Fiction; Humorous stories; Squirrels -- Juvenile fiction; Beaches -- Juvenile fiction; Friendship -- Juvenile fiction; Picture books; Humorous fiction; Animal fiction; Readers (Publications)